APROPRIAÇÕES EPISTEMOLÓGICAS PRATICADAS NOS TRABALHOS DA ANPED SOBRE FORMAÇÃO CONTINUADA DE PROFESSORES (2008 – 2019) - Astori, Fernanda Bindaco da Silva (2021)
This study analyzes the practices of research and continuing education in the work of the Study Groups (GTs, in portuguese) of the National Association for Graduate Studies and Research in Education (ANPEd), from the 31st to the 39th national meetings, from 2008 to 2019. It prioritized, the methodological operations in use and the theories in circulation, from the perspective that ANPEd offers clues to the epistemologies that mark the paths of academic production on teacher education in Brazil. This thesis embraces the assumptions of a qualitative approach, guided by the resources of historical research, referenced by Michel de Certeau, from the bibliographical documentary methodology, in the analysis of the 165 works resulting from oral communication, available on the association's website. It defends that research practices on the continuing education of teachers take place between the SGs and show that the knowledge produced is interdisciplinary, in areas of dialogue marked by correlations of forces and bricolage in the appropriation of theories and methodologies. SGs employ their own logics that mark their fields of research, in a movement of epistemological (dis)continuities in which the SG-08 acts as an inducer of theories and methodologies that create orders, establish pertinence, delimit social positions, stress knowledge and point out new challenges for academic research. Observing the micro-differences in the ways of doing research and continuing education. Also, it reveals that the problematization of research takes place around issues of the teaching process, pedagogical practice, professional development, the meanings attributed to practice and continuing education, with the objective of offering contributions to the training process and to the teaching work. It highlights collaborative experiences through research methodologies connected to the intervention. Besides that, this work tensions theorizations and criticisms about policy formulation processes, their content and their implications in the contexts of continuing teacher education practices. Plus, it defines the social positions of research by defending continuing education with institutional links, emphasizing the responsibility of teaching networks and universities to mediate relations between teaching, research and extension. Furthermore, it targets that continuing education, investigated in several SGs, is an emerging subject in research and an educational problem. It also demonstrates that there is a strong GT-08’s institutionality in the demarcation of references and field culture. It shows the circularity of authors in the SGs and SG-08, the structuring assumptions of the debates, the most appropriate works and concepts, as well as the correlations of forces between competing rationalities in the epistemologies of academic research on the continuing education of teachers. It underscores as challenges for research and for the practices of continuing education the need for revisions of different natures, especially in the theoretical-methodological foundation.